KONTRIBUSI SUPERVISI PENGAWAS MADRASAH DAN MOTIVASI KERJA GURU TERHADAP KINERJA GURU MTS SEKECAMATAN SUNGAI TARAB - Hendri Marita (IAIN Batusangkar, 2016)
Contributions Supervision of Trustees Madrasah and Work Motivation to Teachers Performance MTs se-Kecamatan Sungai Tarab. On the basis preliminary field observation, the researcher noticed that the Kecamatan Sungai Tarab Islamic Junior High School Teacher’s performance was relatively low. It was presumed that the teacher’s low performance was caused by of the school supervision and low motivation of the teacher’s. This research was intended to find out the contribution of the school supervision and motivation to ward the teacher’s performance. There is hypotheses to be tested: Supervision contributed significantly toward the teacher’s performance. Research population were all teacher’s of Islamic junior high school consisting of 58 teacher’s were selected as a research sample by means of stratified random sampling technique. The result of data analyses show that The supervision of the school contributed significantly (50,9%) to ward the teacher’s performance.. It is then concluded that the supervision is important factors that may influence the performance of Kecamatan Sungai Tarab Islamic Junior High School teacher’s, yet not to ignore other factors which are not treated in this research. Based on the research findings it is recommended that the two researched factors be paid more attention in order to improve and increase the teacher’s performance. Kata Kunci : Supervisi pengawas, kinerja guru